ERGONOMICS AND PRODUCTIVITY - Solano Cuyubamba, Jesús (1999)
The article shows the relationship between ergonomics and Industrial Engineering, and how that influences the production levels achieved. Similarly, it is noted how ergonomics design poses a new job, which allows an increase in efficiency, safety and productivity.